Sex specific activation of the ERα axis of the mitochondrial UPR (UPRmt) in the G93A-SOD1 mouse model of familial ALS. (10th February 2017) - Riar, Amanjot K; Burstein, Suzanne R; Palomo, Gloria M.; Arreguin, Andrea; Manfredi, Giovanni; Germain, Doris
Abstract: The mitochondrial unfolded protein response (UPR mt ) is a transcriptional program aimed at restoring proteostasis in mitochondria. Upregulation of mitochondrial matrix proteases and heat shock proteins was initially described. Soon thereafter, a distinct UPR mt induced by misfolded proteins in the mitochondrial intermembrane space (IMS) and mediated by the estrogen receptor alpha (ERα), was found to upregulate the proteasome and the IMS protease OMI. However, the IMS-UPR mt was never studied in a neurodegenerative disease in vivo . Thus, we investigated the IMS-UPR mt in the G93A-SOD1 mouse model of familial ALS, since mutant SOD1 is known to accumulate in the IMS of neural tissue and cause mitochondrial dysfunction. As the ERα is most active in females, we postulated that a differential involvement of the IMS-UPR mt could be linked to the longer lifespan of females in the G93A-SOD1 mouse. We found a significant sex difference in the IMS-UPR mt, because the spinal cords of female, but not male, G93A-SOD1 mice showed elevation of OMI and proteasome activity. Then, using a mouse in which G93A-SOD1 was selectively targeted to the IMS, we demonstrated that the IMS-UPR mt could be specifically initiated by mutant SOD1 localized in the IMS. Furthermore, we showed that, in the absence of ERα, G93A-SOD1 failed to activate OMI and the proteasome, confirming the ERα dependence of the response. Taken together, these results demonstrate the IMS-UPR mt activation in SOD1 familial ALS, and suggest that sex differences in the disease phenotype could be linked to differential activation of the ERα axis of the IMS-UPR mt .